Digital economy, institutional quality and economic growth in selected countries - Olabode Philip Olofin (CBN Journal of Applied Statistics, 2023)
This study examines the role of digital economy and institutional quality on economic growth of Bangladesh, Ethiopia, Kenya, and Nigeria. The study adopts the feasible generalized least square method with annual panel data from 1985 to 2017. Results show that digital economy, human capital and knowledge worker, and democratic accountability promote economic growth, while corruption, socioeconomic conditions, and bureaucratic quality retard economic growth. Furthermore, interaction of digital economy with corruption promotes growth. However, the interaction of digital economy with institutional quality retards economic growth, which could be due to the deteriorating institutional quality and low level of economic digitalization in these countries. The study concludes that digital economy and institutional quality could play positive roles in the quest to becoming emerging markets. The study suggests more involvement of the countries in digital economy and improved institutional quality.
Keywords: D73; D83; E02; O33; 330; Digital economy; economic growth; institutional quality